Defining the psychiatric and financial burden of mental and substance use disorders in cancer patients. (19th December 2022) - Baliga, Sujith; Klamer, Brett; Palmer, Joshua D.; Gregirio, Sharla Wells‐Di; Kale, Sachin S.; Bonomi, Marcelo; Old, Matthew O.; Rocco, James W.; Blakaj, Dukagjin M.
Abstract: Purpose: To identify the proportion of Emergency Department (ED) visits in cancer patients associated with a mental and substance use disorder (MSUD) and the subsequent healthcare costs. Methods: Nationally representative data on ED visits from 2009 to 2018 was obtained from the Nationwide Emergency Department Sample (NEDS). We identified cancer‐related visits with or without a MSUD using the Clinical Classifications Software diagnoses documented during the ED visit. Survey‐adjusted frequencies and proportions of ED visits among adult cancer patients with or without a MSUD was evaluated. Survey‐adjusted multivariable logistic regression models were used to examine demographic and clinical predictors of the presence of an MSUD and the likelihood of hospital admission for patients with a primary MSUD. Results: Among 54, 004, 462 ED visits with a cancer diagnosis between 2009 and 2018, 11, 803, 966 (22%) were associated with a MSUD. Compared to a primary diagnosis of cancer, patients who presented to the ED with a chief complaint of MSUD were more likely to be female (54% vs. 49%), younger (median: 58 vs. 66), more likely to have Medicaid insurance, and more likely to be discharged home. The three most common MSUD diagnoses among cancer patients were alcohol‐related disorders, anxiety disorders, and depressive disorders. The total costs associated with a primary MSUD from 2009 to 2018 was 3, 133, 432, 103, of which alcohol‐related disorders claimed the largest majority. Younger age (OR per 10‐year increase: 0.86, 95% CI: 0.85, 0.86) and female sex (OR: 1.34, 95% CI: 1.33–1.35) were associated with higher odds of having an MSUD. Conclusions: Our findings demonstrate a high burden of psychiatric and substance use illness in the cancer population and provide the rationale for early psychosocial intervention to support these patients. Abstract : These findings demonstrate a high rate of mental and substance use disorder (MSUD) in cancer patients with one in five cancer‐related visits to the ED presenting with a MSUD. Younger age and female gender were more likely associated with mental or substance use disorders. Healthcare costs for MSUD were 3 billion dollars over 10 years.